The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3390/ijms21041276
|View full text |Cite
|
Sign up to set email alerts
|

TLR4 Stimulation Promotes Human AVIC Fibrogenic Activity through Upregulation of Neurotrophin 3 Production

Abstract: Background: Calcific aortic valve disease (CAVD) is a chronic inflammatory disease that manifests as progressive valvular fibrosis and calcification. An inflammatory milieu in valvular tissue promotes fibrosis and calcification. Aortic valve interstitial cell (AVIC) proliferation and the over-production of the extracellular matrix (ECM) proteins contribute to valvular thickening. However, the mechanism underlying elevated AVIC fibrogenic activity remains unclear. Recently, we observed that AVICs from diseased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…[20] Additionally, BMP2 is a marker of vascular cells' osteogenic phenotypic change, which is a critical mechanistic step in the development of CAVD. [21] Kim et al [18] found that COMP can directly bind to the C-terminus of BMP2, as confirmed by Co-IP and GST pull-down assays. Consistently, we found that COMP and BMP2 were co-located in CAVD group valves in this study.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…[20] Additionally, BMP2 is a marker of vascular cells' osteogenic phenotypic change, which is a critical mechanistic step in the development of CAVD. [21] Kim et al [18] found that COMP can directly bind to the C-terminus of BMP2, as confirmed by Co-IP and GST pull-down assays. Consistently, we found that COMP and BMP2 were co-located in CAVD group valves in this study.…”
Section: Discussionmentioning
confidence: 84%
“…BMP2 and transforming growth factor-β (TGF-β) can mediate biglycan-induced pro-osteogenic reprogramming in aortic valve interstitial cells [20] . Additionally, BMP2 is a marker of vascular cells’ osteogenic phenotypic change, which is a critical mechanistic step in the development of CAVD [21] . Kim et al [18] found that COMP can directly bind to the C-terminus of BMP2, as confirmed by Co-IP and GST pull-down assays.…”
Section: Discussionmentioning
confidence: 96%
“…As mentioned before, TLRs and neutrophin 3 are involved in myofibroblast activation (118). Neutrophin neutralization using specific antibodies or inhibition of the downstream signaling was shown to inhibit the activation in vitro; whether a clinical application is thinkable needs to be evaluated.…”
Section: Regression Of Fibrosis Molecular Targets and Potential Pitfalls In Pharmaceutical Interventionsmentioning
confidence: 97%
“…Stimulation of TLR4 with lipopolysaccharide activates the Akt and ERK1/2 pathway and increases the expression of neurotrophin 3. This activation subsequently results in VIC proliferation and increased collagen 3 and MMP9 production with implications for pathological ECM remodeling ( 118 ).…”
Section: Molecular Mechanisms Of Valvular Fibrosis and Potential To Reverse Remodelingmentioning
confidence: 99%
“…Moreover, we observed that human AVICs express functional Toll-like receptors (TLRs), and AVICs isolated from diseased aortic valves have higher levels of TLR2 and TLR4 [10]. More importantly, stimulation of TLRs in human AVICs not only induces inflammatory responses [7][8][9]11], but also elevates cellular osteogenic and fibrogenic activities [8][9][10][12][13][14], and the pro-inflammatory and pro-osteogenic pathways in human AVICs interact to modulate cellular inflammatory and osteogenic activities [15]. Thus, TLRs may play a mechanistic role in mediating CAVD progression [16].…”
Section: Ivyspring International Publishermentioning
confidence: 99%